PECULIARITIES OF FORMATION OF THE BELARUSIAN SCIENTIFIC LANGUAGE AT THE BEGINNING OF THE ХХ - Любецкая, Е. П. (Zapysky z ukraïnsʹkoho movoznavstva = Opera annua in linguistica ukrainiana, 2017)
The purpose of the work is to determine the peculiarities of the formation of the Belarusian scientific language. Objectives of the research: consideration of ways of the Belarusian scientific language formation through the prism of terminology. The object of the research is the Belarusian scientific language, the subject - approaches to its development in the early twentieth century. In the initial period of the formation of the Belarusian scientific language the existence of different variants of its formation can be identified (natural way and conscious terminological approach as a result of language policy).